Baby Business: a randomised controlled trial of a universal parenting program that aims to prevent early infant sleep and cry problems and associated parental depression - Cook Fallon; Bayer Jordana; Le Ha ND; Mensah Fiona; Cann Warren; Hiscock Harriet (BMC, 2012)
Abstract Background Infant crying and sleep problems (e.g. frequent night waking, difficulties settling to sleep) each affect up to 30% of infants and often co-exist. They are costly to manage and associated with adverse outcomes including postnatal depression symptoms, early weaning from breast milk, and later child behaviour problems. Preventing such problems could improve these adverse outcomes and reduce costs to families and the health care system. Anticipatory guidance-i.e. providing parents with information about normal infant sleep and cry patterns, ways to encourage self-settling in infants, and ways to develop feeding and settling routines before the onset of problems-could prevent such problems. This paper outlines the protocol for our study which aims to test an anticipatory guidance approach. Methods/Design 750 families from four Local Government Areas in Melbourne, Australia have been randomised to receive the Baby Business program (intervention group) or usual care (control group) offered by health services. The Baby Business program provides parents with information about infant sleep and crying via a DVD and booklet (mailed soon after birth), telephone consultation (at infant age 6-8 weeks) and parent group session (at infant age 12 weeks). All English speaking parents of healthy newborn infants born at > 32 weeks gestation and referred by their maternal and child health nurse at their first post partum home visit (day 7-10 postpartum), are eligible. The primary outcome is parent report of infant night time sleep as a problem at four months of age and secondary outcomes include parent report of infant daytime sleep or crying as a problem, mean duration of infant sleep and crying/24 hours, parental depression symptoms, parent sleep quality and quantity and health service use. Data will be collected at two weeks (baseline), four months and six months of age. An economic evaluation using a cost-consequences approach will, from a societal perspective, compare costs and health outcomes between the intervention and control groups. Discussion To our knowledge this is the first randomised controlled trial of a program which aims to prevent both infant sleeping and crying problems and associated postnatal depression symptoms. If effective, it could offer an important public health prevention approach to these common, distressing problems. Trial registration number ISRCTN: ISRCTN63834603